Barriers to asymptomatic screening and other STD services for adolescents and young adults: focus group discussions - Leone Peter A; Smurzynski Marlene; Ford Chandra L; Sanchez Victoria; Tilson Elizabeth C; Fox Kimberley K; Irwin Kathleen; Miller William C (BMC, 2004)
Abstract Background Sexually transmitted diseases (STDs) are a major public health problem among young people and can lead to the spread of HIV. Previous studies have primarily addressed barriers to STD care for symptomatic patients. The purpose of our study was to identify perceptions about existing barriers to and ideal services for STDs, especially asymptomatic screening, among young people in a southeastern community. Methods Eight focus group discussions including 53 White, African American, and Latino youth (age 14-24) were conducted. Results Perceived barriers to care included lack of knowledge of STDs and available services, cost, shame associated with seeking services, long clinic waiting times, discrimination, and urethral specimen collection methods. Perceived features of ideal STD services included locations close to familiar places, extended hours, and urine-based screening. Television was perceived as the most effective route of disseminating STD information. Conclusions Further research is warranted to evaluate improving convenience, efficiency, and privacy of existing services; adding urine-based screening and new services closer to neighborhoods; and using mass media to disseminate STD information as strategies to increase STD screening.